Glycosylated Hemoglobin (HbA1c) as a Marker for Dyslipidemia in Type 2 Diabetes Mellitus - Henna Khalid, Mariam Riaz, Momina Khadija Abbasi, Abdul Haseeb (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to examine the effectiveness of HbA1c as a predictor of dyslipidemia in patients with Type-2 Diabetes Mellitus. Study Design: Cross-sectional Place and Duration: Department of Pathology; Women Medical & Dental College Abbottabad in collaboration with Jinnah International Hospital, Abbottabad; April 2022 – September 2022 Methods: After obtaining their agreement, a total of 110 people with Type-2 diabetes mellitus were included in the research. Statistics and background information were recorded. Fasting lipid profile (cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, and cholesterol/HDL), HbA1c, creatinine, and electrocardiogram were conducted as part of the comprehensive systemic examination to detect the presence of complications or co-morbidities. Mean, frequency, and correlation analyses are performed in SPSS 22.0. When doing a correlation analysis, the Pearson Chi-square test was typically utilized. Results: Twenty-two patients (20%) had an HbA1c below 7%, whereas eighty-eight patients (80%) had a HbA1c beyond 7%. Dyslipidemia was seen in 62 individuals (56.4%). Direct connections were found between HbA1c and BMI, cholesterol, triglycerides, and low-density lipoprotein (LDL), while an inverse correlation was found between HbA1c and high-density lipoprotein (HDL). When comparing female and male patients, females were shown to have considerably greater TG levels. HbA1c levels were also significantly correlated with the presence of metabolic syndrome, particularly among women (P0.003). Conclusion: According to the findings of our research, HbA1c is not only useful as a biomarker of long-term glycaemic control, but it is also an excellent predictor of lipid profile. Keywords: Lipid Profile, Dyslipidemia, Type 2 Diabetes mellitus, HbA1c